The Effect Of Quantum Teaching Learning Model To Enhance Students’ Conceptual Understanding on Characteristic Material Concept - Dewi, Ravita; Alpusari, Mahmud; N, Lazim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research aims to investigate effect of quantum teaching learning model to enhance students’ conceptual understanding on characteristic material concept. This study method was experiment with quasy experiment. Subject this research was fifth grade elementary school. Result of this study found significant score 0,000 < 0,05. It is mean that hypothesis of research was accepted. It can be concluded Quantum Teaching learning model can improve students’ conceptual understanding.